2019
DOI: 10.1002/jum.14970
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Findings of Mammary Duct Ectasia Causing Bloody Nipple Discharge in Infancy and Childhood

Abstract: Bloody nipple discharge in infancy and childhood is extremely rare, and mammary duct ectasia is the most common etiology. Ultrasound (US) findings of mammary duct ectasia include dilated ducts and tubular anechoic lesions that may contain echogenic debris in the subareolar region. However, mammary duct ectasia may show variable US findings, which are not well described in the literature. We report 3 cases of mammary duct ectasia in infancy and childhood with variable imaging findings, including complex cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The patient only shows signs of nipple or areola pain and a "cheese"-like excretion on nipple squeezing. On ultrasound examination, the lesion is mostly flat, and the blood flow is sparse, with low velocity and low resistance [17][18][19]. Molybdenum target examination of the mammary gland shows an asymmetrical shadow with an increased density, a flame-like appearance, an uneven density accompanied by low-density tubular structures and scattered rod-shaped or hollow, small, round calcified shadows along the long axis of the catheter.…”
Section: Duct Dilatation Stagementioning
confidence: 99%
“…The patient only shows signs of nipple or areola pain and a "cheese"-like excretion on nipple squeezing. On ultrasound examination, the lesion is mostly flat, and the blood flow is sparse, with low velocity and low resistance [17][18][19]. Molybdenum target examination of the mammary gland shows an asymmetrical shadow with an increased density, a flame-like appearance, an uneven density accompanied by low-density tubular structures and scattered rod-shaped or hollow, small, round calcified shadows along the long axis of the catheter.…”
Section: Duct Dilatation Stagementioning
confidence: 99%
“…The cystic lesions may be small and simple, or larger and multiseptated or complex (9-12). Moon et al reported 3 cases of mammary duct ectasia in infancy and childhood, with variable imaging findings, including complex cystic and solid lesions (13). Bilateral ductal dilatations were detected on ultrasonography in our two cases.…”
Section: Discussionmentioning
confidence: 46%